TASTE AVERSION LEARNING: CHARACTERISTICS, PARADIGM AND BRAIN MECHANIMS - Molero Chamizo, Andrés (Anales de Psicología / Annals of Psychology, 2007)
The acquisition of the association between a taste and visceral disease can be vital for numerous species, because of the learned aversion could prevent the effects of a continuous poisoning. This condi-tioning has some special features with regard to the most of associative learnings. Taste aversion learning is a paradigm very used in animal re-search about learning and memory. Although lesser frequently, conditioning taste aversion has been researched in human as well. The present review evaluates the taste aversion learning paradigm in animals, and the results of the research about his biological bases. Also, they will be dis-cussed some current finds about the human brain mechanisms of the food behaviour and theirs relationship with the neurobiology of taste aversion learning.